Approaching High Functioning Autism of Middle Aged and Elder People - Συριοπούλου-Δελλή Χριστίνα; Πάσουλα Ειρήνη (Education Sciences, 2021)
Individuals with autism spectrum disorder (ASD) are characterised by difficulties in social communication and social interaction alongside unusually restricted, repetitive behaviour and interests. IQ. High-functioning individuals with autism have average or higher intelligence. The lack of intellectual disability does not mean, though, that they can simply overcome inherent social difficulties; they typically struggle to communicate effectively in a neurotypical world, manage daily tasks and survive at workplaces. They are at increased risk of having medical, developmental or psychiatric conditions. The present article examines a less researched issue, how high functioning persons with autism experience middle and old age. Their trajectories into these periodsof life are discussed with reference to factors such as physical health, anxiety and other mental health disorders, brain functioning and health, psychological resilience and social support. The issue of autism diagnosis during later stages of life is also considered. The article concludes with a synopsis of the above, as well as with the discussion of some wider ideas and suggestions.